Analisis Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) di PT X, Sumatera Selatan - Heriziana.Hz; Santi Rosalina (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Management system safety and health is one of the effort For control risks and dangers at work . So Lots risks and dangers in place work that can threaten health and safety the work of the workers , is expected with the existence of a management system safety and health good job​ so can give place safe work and comfort for workers .​ Risks and dangers can controlled with management system safety and health good job​ sustainable with good commitment​ from companies and workers . Research This is study descriptive observational , namely study This done with collect primary data and secondary data . The number of sample in study These are 94 respondents . The results of the study This show results study implementation of SMK3 at PT. “X” was obtained results implementation of SMK3 has been Good with the Level of Implementation Good as much as 89%, Level of implementation satisfying as much as 8%.